Comparing the Safety between Ferrous Carboxymaltose and Iron Sucrose Therapy in Iron Deficiency Anemia during Pregnancy in Obstetrics and Gynecology Ward at Tertiary Care Hospital, Jaipur - Saini, Kamal; Singh, Rajveer; Agrawal, Divyani (Indian Journal of Pharmacy Practice)
Background: Pregnancy is the most vulnerable condition prone for anemia (most commonly iron deficiency anemia). Hence requires drug therapy for iron store replenishment. Comparing the safety between ferrous carboxymaltose and iron sucrose therapy in iron deficiency anemia during pregnancy in obstetrics and gynecology ward at a tertiary care hospital. Methods: A prospective observational single centered study was conducted on 60 pregnant women who were diagnosed with iron deficiency anemia in the department of obstetrics and gynecology at tertiary care teaching hospital. The subjects were divided into two groups, first group was administered iron sucrose 200mg and second group was administered ferrous carboxymaltose 500mg. The relative incidence of drug administrative adverse event was low in Ferrous Carboxymaltose than compare to Iron Sucrose. Result: The adverse event occurred in 3.33% for Ferrous Carboxymaltose and 13.33% for Iron Sucrose. The mean rise of hemoglobin was 2.92 g/l for Ferrous Carboxymaltose and 1.08 g/l for iron sucrose. Conclusion: In this study it was found that Ferrous carboxymaltose is safer in comparison to the Iron sucrose among the pregnant women with Iron deficiency anemia.
Keywords: Ferrous Carboxymaltose; Iron Sucrose; Iron Deficiency Anemia; Pregnant woman; Haemoglobin.